(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Mucoadhesive drug delivery systems interact with the mucus layer covering the mucosal epithelial surface and increase the residence time of the dosage form at the absorption site. The drugs which have local action or those which have maximum absorption in gastrointestinal tract (GIT) require increased duration of stay in GIT. Thus, mucoadhesive dosage forms are advantageous in increasing the drug plasma concentrations and also therapeutic activity. Silymarin (SLM) is an effective hepatoprotective drug used in therapeutic practice today. However, its absorption is in stomach and needs to be retained in the same for prolonged period. So SLM is suitable candidate to develop into mucoadhesive drug delivery system. The objective of the present study was to formulate mucoadhesive microspheres of Silymarin and carryout evaluation of the formulated microspheres. In the present study, five formulations of microspheres with variable concentrations of mucoadhesive polymer and film forming polymer (HPMC & EC) were prepared by Emulsification solvent evaporation method and evaluated for physico-chemical, preformulation and formulation parameters. Compatibility studies proved that there was no interaction between Silymarin and polymers used. Silymarin microspheres were smooth and spherical in nature, which was confirmed by SEM. The in vitro performance of SLM microspheres showed controlled release depending on the concentration of mucoadhesive polymer. Finally it can be concluded that mucoadhesive microspheres encapsulated with optimum concentration of mucoadhesive polymer and film forming polymer showed better results in all the evaluated parameters making it a potential candidate for controlled release drug delivery system.